Renaissance of the tooth fairy!!! - Behl, Manisha; Jindal, Samriti; Sharma, Shivani; Shahi, Priyanka; Shahi, Nishat; Khanna, Vikram (International Journal of Dental Research, 2014)
Regenerative endodontic procedures have brought novelty in the arena of dentistry. Stem cell research has paved its way into conserving and utilizing the multipotent stem cells for tissue growth. One such procedure is revascularization which utilizes the apical stem cells for root lengthening and reinforcement in traumatized tooth with an open apex. The present clinical case report has shown that revascularization results in successful root lengthening and apical closure in lesser appointments than conventional specification procedure without weakening the dentinal walls.   Keywords: Regenerative endodontics, stem cell research, revasularisation, open apex, apexification.